Examining Ukraine’s EU Candidate Status: (When) Does the Accession Process Turn from Political to Legal? - Christoph Schewe; Arnis Buka; Edmunds Broks (Law: Journal of the University of Latvia)
This article explores the nature of the notion “candidate country status” in the context of EU accession. In particular it enquires whether the candidate status, which was granted to Ukraine by the European Council on 23 June 2022, has any actual legal implications or is the whole accession process up to the point where accession agreement is signed entirely devoid of legal consequences. Legal doctrine seems to generally answer this question in the affirmative, explaining that the candidate status was a rather political concept bearing primarily symbolic relevance. However, the example of Ukraine, which was granted candidate status much more rapidly than a number of other countries before it, challenges to explore the topic in more depth, in particular by delving into the CJEU’s existing case law on candidate status and the possibility of challenging the granting of candidate status through litigation in the CJEU.